Characterization of volatile compounds and microbial diversity of Arabica coffee in honey processing method based on different mucilage retention treatments - Faguang Hu; Haohao Yu; Xingfei Fu; Zhongxian Li; Wenjiang Dong; Guiping Li; Yanan Li; Yaqi Li; Bingqing Qu; Xiaofei Bi (Food Chemistry: X)
This study combined HS-SPME-GC–MS and high-throughput sequencing to explore how honey-processing methods with varying mucilage retentions impact volatile compounds and microbial communities in green coffee beans. HS-SPME-GC–MS revealed that the RH group (75 % to 80 % mucilage retention) had the highest relative content of volatile compounds. According to rOAV >1, 13 key aroma compounds were identified, contributing to flavors like “mellow” and “fruity”. High-throughput sequencing identified seven dominant bacterial genera and four dominant fungal genera, with higher diversity of fungi than bacteria across treatments. Correlation analysis indicated that bacteria and fungi contribute to aroma formation, with bacteria more active in low-mucilage and fungi in high-mucilage treatments. Overall, the RH group was optimal for the aroma quality and bioactivity of green coffee beans. The findings of this research offers insights into aroma compound-microbe interactions in coffee mucilage fermentation, helping coffee producers optimize process parameters for better-quality coffee products.